2014
DOI: 10.1586/14787210.2014.870884
|View full text |Cite
|
Sign up to set email alerts
|

The early bactericidal activity of antituberculosis drugs

Abstract: Early bactericidal activity studies measure the ability of antituberculosis treatments to reduce the burden of Mycobacterium tuberculosis in sputum specimens collected overnight from smear-positive pulmonary tuberculosis patients during the first 14 days of therapy. This confirms the efficacy of novel agents or drug combinations in human patients, allows comparison of different drug dosages and a preliminary assessment of the drugs' pharmacokinetics and toxicity in closely observed patients. In the past few ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 61 publications
1
38
0
Order By: Relevance
“…In contrast to dose-fractionation studies, EBA studies do not break the collinearity of PK/PD parameters. [10,13] For most anti-TB drugs, the AUC 0-24 h relative to the MIC has been suggested as the best parameter to predict in vivo efficacy of drugs against Mtb. [9][10][11]14] As only unbound drug is active, the free AUC is often used as a target.…”
Section: Pk/pdmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to dose-fractionation studies, EBA studies do not break the collinearity of PK/PD parameters. [10,13] For most anti-TB drugs, the AUC 0-24 h relative to the MIC has been suggested as the best parameter to predict in vivo efficacy of drugs against Mtb. [9][10][11]14] As only unbound drug is active, the free AUC is often used as a target.…”
Section: Pk/pdmentioning
confidence: 99%
“…This study shows that when a mean MIC of TB isolates is known, the EBA that is found in human EBA studies is mediated through an AUC 0-24 h /MIC ratio that is achieved in an in vitro TB model. [13,17] The AUC 0-24 h was also linked to treatment outcome in the study of Pasipanodya et al (2013). They showed that the AUC of pyrazinamide, rifampicin, and isoniazid below a certain threshold, were predictors of a poor long-term outcome.…”
Section: Efficacymentioning
confidence: 99%
“…The therapist uses the mycobacterial count in sputum to follow the impact of combination therapy and to adjust its length. Clinical trialists subject sputum to the early bactericidal activity test as a gateway through which any new TB drug candidate must pass if it is to go on to larger, longer, and far more expensive tests of efficacy in combination with other drugs (4).…”
Section: New Evidence For the Complexity Of The Population Structure mentioning
confidence: 99%
“…This method provides reproducible results regarding efficacy although it does not reliably predict sterilising activity. The technique is mainly used for dose finding and preliminary evaluation of toxicity in a small sample [102] up to 14 days. Using this approach to evaluate PA-824, it has been shown that the mean multi-agent 14-day EBA of PA-824, moxifloxacin and pyrazinamide is comparable with that of the current standard treatment and significantly higher than those of bedaquiline, bedaquiline with pyrazinamide, and bedaquiline with PA-824 [47].…”
Section: Novel Designs For Clinical Trialsmentioning
confidence: 99%